1987
DOI: 10.1007/bf00156230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural landscape structure on energy flow and water cycling

Abstract: In long term studies the following climatological characteristics were measured or calculated: air and soil temperature, sunshine, wind speed, vapor pressure, saturation deficit, precipitation, humidity, incoming and reflected solar energy, energy emitted by active surfaces and primary production. Taking into account the relationships between climatological characteristics, the growth stages of vegetation, and relations between heat balance components, the fluxes of energy used for evapotranspiration, air, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 3 publications
0
41
0
Order By: Relevance
“…Measurements of energy fluxes at the landscape level, which requires an enormous recording infrastructure, have been reported in rare cases, such as in Ryszkowski and Kędziora (1987), but, to date, no study has provided a sufficient level of integrative results to evaluate the link between spatial heterogeneity at the landscape scale and entropy. Therefore, any statement specifying a link, direct or inverse, between spatial heterogeneity and thermodynamic entropy should be treated with caution.…”
Section: Spatial Heterogeneity: Contested Thermodynamic Correspondencementioning
confidence: 99%
“…Measurements of energy fluxes at the landscape level, which requires an enormous recording infrastructure, have been reported in rare cases, such as in Ryszkowski and Kędziora (1987), but, to date, no study has provided a sufficient level of integrative results to evaluate the link between spatial heterogeneity at the landscape scale and entropy. Therefore, any statement specifying a link, direct or inverse, between spatial heterogeneity and thermodynamic entropy should be treated with caution.…”
Section: Spatial Heterogeneity: Contested Thermodynamic Correspondencementioning
confidence: 99%
“…The more intensive is the surface evaporation, the less energy remains for heating air (table 1). Bare soil uses five times more energy than forests or water bodies for air heating (Ryszkowski and Ke˛dziora 1987).…”
Section: An Essential Task Must Be To At Least Reverse the Ongoing Trmentioning
confidence: 99%
“…The incoming long wave radiation (L) have been estimated from ten years average air temperature, applying the Stefan-Boltzmann law. In order to calculate the absorpivities of the solar radiation, it has been necessary to know the albedo of different surfaces; this values and the emissivities of different surfaces were derived from researches of different authors (Morgan et al, 1977;Ryszkowski and Kę dziora, 1987) and are indicated in Table 2.…”
Section: The Energy Balance Modelmentioning
confidence: 99%